Anti-Androgen Receptor Therapies in Prostate Cancer: A Brief Update and Perspective - Huang, Jian; Lin, Biyun; Li, Benyi (Frontiers in Oncology, 2022)
Prostate cancer is a major health issue in western countries and is the second leading cause of cancer death in American men. Prostate cancer depends on the androgen receptor (AR), a transcriptional factor critical for prostate cancer growth and progression. Castration by surgery or medical treatment reduces androgen levels, resulting in prostatic atrophy and prostate cancer regression. Thus, metastatic prostate cancers are initially managed with androgen deprivation therapy. Unfortunately, prostate cancers rapidly relapse after castration therapy and progress to a disease stage called castration-resistant prostate cancer (CRPC). Currently, clinical treatment for CRPCs is focused on suppressing AR activity with antagonists like Enzalutamide or by reducing androgen production with Abiraterone. In clinical practice, these treatments fail to yield a curative benefit in CRPC patients in part due to AR gene mutations or splicing variations, resulting in AR reactivation. It is conceivable that eliminating the AR protein in prostate cancer cells is a promising solution to provide a potential curative outcome. Multiple strategies have emerged, and several potent agents that reduce AR protein levels were reported to eliminate xenograft tumor growth in preclinical models via distinct mechanisms, including proteasome-mediated degradation, heat-shock protein inhibition, AR splicing suppression, blockage of AR nuclear localization, AR N-terminal suppression. A few small chemical compounds are undergoing clinical trials combined with existing AR antagonists. AR protein elimination by enhanced protein or mRNA degradation is a realistic solution for avoiding AR reactivation during androgen deprivation therapy in prostate cancers.